The Causes of Awaiting Trial of Inmates in Nigerian Correctional Service: A Case Study of Jos Correctional Center - Uwais, Idrees Abdullahi; Sulaiman, Usman Muhammad; Gwani, Abdullatif Isa (International Journal of Humanities, Education, and Social Sciences, 2025)
This study investigates the issue of awaiting trial as a systemic challenge within Nigeria’s correctional system, with a specific focus on Jos Correctional Service. The objective is to examine the nature of the practice, identify investigative and judicial failures, explore contributing factors, assess its effects on inmates, and propose viable solutions. A total of 100 respondents were selected from five units within Jos Correctional Service, comprising 80 awaiting trial inmates, 5 correctional service officials, 5 representatives from the High Court, and 10 personnel from the Nigeria Police Force. Data were collected using structured questionnaires, with quantitative data analyzed using frequency distribution tables, while qualitative responses were analyzed descriptively. Literature was reviewed from academic journals, magazines, and newspapers to support the findings. Results reveal that prolonged detention of suspects without trial contradicts the constitutional principle of presumption of innocence, often resulting from delayed investigations, judicial bottlenecks, and institutional inefficiencies. The study recommends reforms such as the training of modern, evidence-based police investigators, digitization of court processes to expedite case handling, and the adoption of modern correctional practices, including consideration of privatized prison models. In conclusion, the problem of awaiting trial is a pressing socio-legal issue that undermines justice administration and requires further academic inquiry and urgent institutional reform to uphold human rights and legal standards within Nigeria's correctional framework.